(untitled) (Revista BOEM, 2024)
This article aims to analyze the experiences shared by video producers in the video shows at the VII Festival of Digital Videos and Mathematics Education. The sources of data production are observations and statements made during the video shows developed at the award ceremony at UNESP, Rio Claro, SP, coordinated by the Research Group in Informatics, other Media and Mathematics Education. To analyze the data, we carried out a dialogue with part of the literature and ideas associated with the Human-Beings-With-Media construct. The results indicate that the “voices” of the participants in the VII Festival video show promote participant-organizer-media interactions, highlight the importance of the Video Festival in social and cultural content, in addition to presenting the challenges in video production and movements of changes in the classroom and pedagogical practices. Finally, we reason that videos are produced by collectives of human-beings-with-media, where they become actors in a new system, therefore having the power of action within this new system. The video, in this scenario, becomes an actor in several parts, as well as an artifact and community.